UPAYA PENANGGULANGAN TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR ANTARA HARAPAN DAN KENYATAAN - Pratiwi Ayu Sri Daulat (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
The issue of the implementation of criminal law and crime prevention efforts is quite important for a country that wants a rule of law. Crimes that tend to increase are influenced by the coming of a multidimensional crisis. This has the potential to cause increasingly high crime rates in the community, for example motor vehicle theft has increased from year to year. Crimes committed are organized and neat enough to complicate the authorities in this case the police in uncovering cases of motorized theft. From the description above, the police try to prevent and tackle cases of motorized theft by pre-emptive, preventive and repressive measures, as an example of the causes of theft cases many factors including negligence by owners, perpetrators, and the community and there is no safety key so the perpetrator easily steals for a short time.